External Beam Accelerated Partial Breast Irradiation Yields Favorable Outcomes in Patients with Prior Breast Augmentation - Lei, Rachel Y.; Leonard, Charles E.; Howell, Kathryn T.; Henkenberns, Phyllis L.; Johnson, Timothy K.; Hobart, Tracy L.; Kercher, Jane M.; Widner, Jodi L.; Kaske, Terese; Barke, Lora D.; Carter, Dennis L. (Frontiers in Oncology, 2014)
Purpose: To report outcomes in breast cancer patients with prior breast augmentation treated with external beam accelerated partial breast irradiation (EB-APBI) utilizing intensity-modulated radiotherapy or 3-dimensional conformal radiotherapy, both with IGRT. Materials and Methods: Sixteen stage 0/1 breast cancer patients with previous elective bilateral augmentation were treated post-lumpectomy on institutional EB-APBI trials (01185132 and 01185145 on clinicaltrials.gov). Patients received 38.5 Gy in 10 fractions over five consecutive days. Breast/chest wall pain and cosmesis were rated by patient; cosmesis was additionally evaluated by physician per RTOG criteria. Results: The median follow-up from accelerated partial breast irradiation (APBI) completion was 23.9 months (range, 1.2–58.6). Little to no change in cosmesis or pain from baseline was reported. Cosmetic outcomes at last follow-up were judged by patients as excellent/good in 81.2% (13/16), and by physicians as excellent/good in 93.8% (15/16). Ten patients (62.5%) reported no breast/chest wall pain, five (31.2%) reported mild pain, and one (6.2%) reported moderate pain. All patients remain disease free at last follow-up. The median ipsilateral breast, planning target volume (PTV), and implant volumes were 614, 57, and 333 cm3. The median ratios of PTV/ipsilateral breast volume (implant excluded) and PTV/total volume (implant included) were 9 and 6%. Conclusion: These 16 breast cancer cases with prior bilateral augmentation treated with EB-APBI demonstrate favorable clinical outcomes. Further exploration of EB-APBI as a treatment option for this patient population is warranted.